Investigation of Active Damping Methods for Model-Based-Current-Control Scheme of Single-Phase Grid-Tied VSI with LCL Filter - Komurcugil, Hasan; Kukrer, Osman (IEEE, 2017)
In this paper, the performances of various active damping methods for model-based-current-control (MBCC) of single-phase grid-tied LCL-filtered voltage source inverters (VSIs) are investigated. It is shown that the proposed MBCC approach enforces the inverter current to track its reference in all circumstances provided that the inverter current reference is generated accurately. In this study, a proportional-resonant (PR) controller is used to generate the inverter current reference. Also, it is shown that the dynamics of this tracking can be made faster by adding an additional virtual time constant into the control variable equation. In spite of these features, the closed-loop system is subject to the adverse effects of the LCL resonance. Therefore, the possibilities of adding various active damping methods into the closed-loop system are investigated. Computer simulations are conducted to show the performance of the proposed MBCC approach with various active damping methods.
43rd Annual Conference of the IEEE-Industrial-Electronics-Society (IECON) -- OCT 29-NOV 01, 2017 -- Beijing, PEOPLES R CHINA
Keywords: Grid-tied inverter; active damping; LCL filter; proportional-resonant control